Optimizing the economic evaluation method for calculating the total owning cost of induction motors - Ayman Agha; Khaled Alzaareer; Hudefah Alkashashneh (Bulletin of Electrical Engineering and Informatics, 2026)
This paper presents an approach for estimating the total ownership cost (TOC) of induction motors (IMs) by applying five different economic evaluation methods, each based on specific assumptions. These methods are examined and compared in detail to demonstrate the difference in their implementation and outcomes. In addition to the technical data of the analyzed IM, the methods also consider significant economic factors that affect TOC assessments, such as electricity tariffs, initial investment cost, operating hours, discount rate, and the anticipated lifespan. The proposed approach offers a practical tool to support decision-making when selecting the most economical among different alternatives offered by various manufacturers or venders. A numerical example is presented to demonstrate the application of the proposed work, including detailed calculations with results summarized in tables. The paper concludes by offering practical guidance on selecting the most appropriate economic method for the evaluated scenarios of IM, offering direction to site engineers and decision- makers in balancing technical aspects with long-term economic considerations. The calculation is straightforward and can be performed using standard mathematical tools, illustrating how various factors influence costs and enhancing the reliability of the result. For large-scale analyses, MATLAB provides additional computational efficiency and scalability.